Manual de relacionamento de magistrados com a imprensa - Aguiar, Rosa Dalva Cabral de (2015)
This study had the proposal the development of relationship manual between magistrates and the media.The main objective came from the practical experience in press office with the magistrates of the Tribunal Regional do Trabalho – PB (TRT-PB), where it were identified many difficulties and misunderstandings in the relationship with the media. From the discussion of a theoretical framework that includes journalism, language, Media Training, spokesperson and competences, it was possible to outline a multifaceted approach to build the manual. Regarding the research methodology, this work is defined as an exploratory research, qualitative and applied purpose, because it proposes solving an identified problem in a specific context, in this case, the relationship of the TRT judges with the media. The proposed manual was fully prepared, and thus, it is believed that it is an important instrument of knowledge, helping to build new competences for magistrates, and consequently represents a social contribution by providing improvements in the availability of information through of media communications.